OpenSHMEM and Related Technologies. Experiences, Implementations, and Technologies : Second Workshop, OpenSHMEM 2015, Annapolis, MD, USA, August 4-6, 2015. Revised Selected Papers - Gorentla Venkata, Manjunath; Shamis, Pavel; Imam, Neena; Lopez, M. Graham; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the Second OpenSHMEM Workshop, held in Annapolis, MD, USA, in August 2015. The 12 technical papers and one short position papers presented in this book were carefully reviewed and selected from 17 submissions. The topics of the workshop included extensions to the OpenSHMEM API, implementation of the API for current and emerging architectures, tools to debug and profile OpenSHMEM programs, experience porting applications to the OpenSHMEM programming model, and changes to the OpenSHMEM specification to address the needs of programming exascale systems.
Extending the Strided Communication Interface in OpenSHMEM -- Exploring OpenSHMEM Model to Program GPU-based Extreme-Scale Systems -- Check-pointing approach for fault tolerance in OpenSHMEM -- Proposing OpenSHMEM Extensions Towards a Future for Hybrid Programming and Heterogeneous Computing -- A Case for Non-Blocking Collectives in OpenSHMEM: Design, Implementation, and Performance Evaluation -- An Evaluation of OpenSHMEM Interfaces for Variable-length Collective Operations -- Dynamic Analysis to Support Program Development with the Textually Aligned Property for OpenSHMEM Collectives -- From MPI to OpenSHMEM: Porting LAMMPS Scalable Out-of-core OpenSHMEM Library for HPC Graph 500 in OpenSHMEM -- Accelerating k-NN Algorithm with Hybrid MPI and OpenSHMEM Parallelizing the Smith-Waterman Algorithm using OpenSHMEM and MPI-3 One-Sided Interfaces -- An Extension to OpenSHMEM Teams to Enable Topology-Aware Parallel Programming.
Keywords: Software engineering; Computer Communication Networks; Computer software; Computer science; Logic design; Software Engineering; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Programming Techniques; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters